Systematic Review: Local Wisdom in Interactive E-Modules for Primary Education - Haryanto, Nathania Janani; Marmoah, Sri; Kusdianto, Kusdianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The integration of local wisdom into interactive e-modules has emerged as an important strategy to provide contextual and meaningful learning in primary education. This study aims to examine its application in module development and use through a Systematic Literature Review (SLR) of relevant studies. Findings reveal that such e-modules are mainly implemented in science and social studies, embedding students’ real-life environments and cultural values to enhance motivation, cultural identity, conceptual understanding, and active engagement, while also contributing to character building. These results highlight the potential of local wisdom-based e-modules to support culturally responsive and student-centered learning. However, the review is limited by the scarcity of long-term studies evaluating their sustained effectiveness.